Perancangan Logo sebagai Upaya Meningkatkan Identitas Visual Kecamatan Medan Marelan - Joko Bintarto; John John; Al Erris Gasya Rasu (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
Marelan is one of the 21 districts in the city of Medan. It is widely recognized as a highly visited area and is also the second most densely populated district in the city. Due to the high level of activity and population density, there is a need to enhance the visual identity of Medan Marelan District through the design of a logo. In the logo design process, the author employs both primary and secondary research methods, with a particular emphasis on the 5W+1H and SWOT analysis techniques to generate creative ideas for the logo. Given the numerous potentials that Marelan possesses, the logo is expected to reflect the unique characteristics of the district. With the new logo, it is hoped that Medan Marelan District will have a strong and recognizable visual identity for both residents and visitors, and will continue to support the economic growth of the local government and surrounding communities.